Switching the Post-translational Modification of Translation Elongation Factor EF-P - Volkwein, Wolfram; Krafczyk, Ralph; Jagtap, Pravin Kumar Ankush; Parr, Marina; Mankina, Elena; Macošek, Jakub; Guo, Zhenghuan; Fürst, Maximilian Josef Ludwig Johannes; Pfab, Miriam; Frishman, Dmitrij; Hennig, Janosch; Jung, Kirsten; et al. (Frontiers in Microbiology, 2019)
Tripeptides with two consecutive prolines are the shortest and most frequent sequences causing ribosome stalling. The bacterial translation elongation factor P (EF-P) relieves this arrest, allowing protein biosynthesis to continue. A seven amino acids long loop between beta-strands β3/β4 is crucial for EF-P function and modified at its tip by lysylation of lysine or rhamnosylation of arginine. Phylogenetic analyses unveiled an invariant proline in the -2 position of the modification site in EF Ps that utilize lysine modifications such as Escherichia coli. Bacteria with the arginine modification like Pseudomonas putida on the contrary have selected against it. Focusing on the EF-Ps from these two model organisms we demonstrate the importance of the β3/β4 loop composition for functionalization by chemically distinct modifications. Ultimately, we show that only two amino acid changes in E. coli EF P are needed for switching the modification strategy from lysylation to rhamnosylation.